2023
DOI: 10.1186/s12937-023-00857-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spicy food consumption on overweight/obesity, hypertension and blood lipids in China: a meta‐analysis of cross-sectional studies

Abstract: Background and objectives Effect of spicy food consumption on health has attracted widespread attention in recent years. However, the relationships between spicy food intake and overweight/obesity, hypertension and blood lipid levels remain unclear. A meta-analysis of available observational studies was conducted in order to explore the associations. Methods PubMed, Embase, Cochrane Library and Web of science databases were searched for studies pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 61 publications
2
5
0
Order By: Relevance
“…In this research, a positive association was evidenced: the greater the consumption of CAP, the higher the level of adiposity. This is consistent with the results of previous epidemiological studies showing positive associations between chili intake and obesity measurements based on BMI, HC and BAI [19][20][21][22][23][24]. However, an important point of discussion is that the previous studies analyzing the associations between CAP intake and obesity status focused on the consumption levels of…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this research, a positive association was evidenced: the greater the consumption of CAP, the higher the level of adiposity. This is consistent with the results of previous epidemiological studies showing positive associations between chili intake and obesity measurements based on BMI, HC and BAI [19][20][21][22][23][24]. However, an important point of discussion is that the previous studies analyzing the associations between CAP intake and obesity status focused on the consumption levels of…”
Section: Discussionsupporting
confidence: 91%
“…Other studies on Asians similarly evidenced positive associations between a spicy taste and the consumption of chilies and spicy foods with general and abdominal obesity levels [21][22][23]. Indeed, a meta-analysis of the available cross-sectional studies revealed an increased risk of being overweight/obese in individuals in the largest category of spicy food intake compared to those in the smallest category [24]. Thus, further studies are needed to elucidate the association of CAP with body adiposity and metabolic features, taking into account the characteristics of the study populations as well as the cultural and related environmental factors of each region.…”
Section: Introductionmentioning
confidence: 87%
“…Spices were also found to have a lowering effect of BP including capsaicin, pepper, chilli, ginger, garlic, onion, fenugreek, turmeric, which are variously used in different culture foods. This effect could be attributed to the role of transient receptor potential vanilloid 1 (TRPV1) activation 49 . Although, studies on this receptor have not been validated in humans yet 50 .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the impact of spicy food consumption on health also has received widespread attention in recent years. Epidemiological studies have shown that the intake of spicy foods may have beneficial effects on hypertension, gastric ulcers, inflammatory bowel disease and gastrointestinal cancer [ 116 , 117 , 118 ]. And it is negatively correlated with the risk of death caused by cancer, ischemic heart disease and respiratory diseases [ 119 ].…”
Section: Agonists and Antagonists Of Trpv1mentioning
confidence: 99%